A FÉ COMO ESTADO DE PREOCUPAÇÃO ÚLTIMA Interpretação da noção de risco da fé na obra de Paul Tillich - Baleeiro, Cleber Araújo Souto (2017)
The subject that we are discussing is the relationship between faith and risk in Paul Tillich's thinking. We chose to start from some texts of his maturity, especially Systematic Theology and the Dynamics of Faith, but dialoguing with other texts, including the German period. We seek to interpret the theme from an ontological-existential perspective, which means that faith is not treated only as a kind of knowledge, experience or belief, but as the state of the human being taken by a supreme concern. The risk, in this sense, can not also be referring to the contents of faith, but to this state of supreme concern. What leads us to propose, from the work of Tillich, that the risk is present and every act of faith, does not invalidate it, but forms part of its constitution. To assume faith is to take the risk it carries. As a means of developing this thesis, we think of a four-part structure. In the first (The Question of Faith in Tillich) we work on the concept of faith as a state of supreme concern. For this, we begin by discussing the problematization of faith in Tillich as a phenomenological question, then we try to establish the concept of faith as dependent on the concept of religion as the supreme concern. Finally, we present four themes that emerge from the understanding of faith as a state: the idea of faith as destiny, the idea of faith as experience, the relationship between the rational and the irrational, and, some distortions of the concept of faith. In the second part (The proper risk of faith) we try to present the notion of risk. We initially identify three places in Tillich's work in which the idea of risk is related to faith, then we present the ideas of frontier and ambiguities of life as close to the idea of risk. In the third part (Language and risk of faith) we present language as a place where risk penetrates faith, as a place that, because of its dynamic and historically situated character, makes it impossible for faith to be comprehended in an absolute way. For this, we begin by discussing the understanding of language in Aristotle and Heidegger as opposing paradigmatic models, and then, we present the discussion on language in Tillich as an alternative to the two, with emphasis on the symbol as the language of faith. In fourth part (The faith that takes the risk) we deal with the implications of assuming the risk as a constitutive element of the faith. We highlight three implications: the idea of truth of faith, the relationship between faith and doubt, and the relationship between doubt and courage.